Hospital Readiness in Implementing Phase One Global Budget Trial in Sumedang District - Wiwin Winarti; Budi Setiawan Djamhur (Research Collaboration Community (RCC), 2023)
BPJS Kesehatan initiated an operational study on the implementation of the INA-CBGs and Global Budget mixed- method hospital payment system. Since 2018, trials have been carried out in 5 districts and 30 hospitals. In contrast to the INA-CBGS system, the Global budget is a method of hospital funding paid in advance by BPJS Kesehatan for all services/activities for one year that in its calculation it will consider the number of services in the previous year, upcoming activities to be carried out, and hospital performance. The trial will carry out in three stages, namely the Non-Risk Global Budget, the Partial Risk Global Budget and the Full Risk Global Budget. In its implementation, although the global budget has been initiated since 2018, the model or formulation in implementing the global budget policy still requires further study. The purpose of this study is to see the process of implementing the trial and obstacles arises to find the most suitable implementation model. The research method used is a qualitative method with a case study approach. The research subjects were Sumedang District General Hospital, Pakuwon Hospital and Harapan Keluarga Hospital. Since September 2020 they begin to receive real quarterly payments with a non-risk stage to hospitals. The amount of withhold used in this study is 30%. The amount of the budget is calculated based on the calculation of the last three years from the hospital's financial records. Preliminary results, shows that this trial is still ongoing and to continue the payment system for the second stage, the hospital withdrawn their participation is this program as there are discrepancies in the way of calculating finances in setting the budget, determining of the amount of risk that must be borne by both parties and the withhold policy. which is considered burdensome by the hospital, especially for regional general hospitals.